KSUSoy YieldCalc: an innovative native Android app to estimate soybean yield before harvest using conventional approach - Bandyopadhyay, Tania (Kansas State University, 2015)
This report considers a native Android application called “KSUSoy YieldCalc” that assists in yield estimation of soybean before harvest following conventional approach. Android is one of the most popular installed base of any mobile platform, powering many mobile devices in more than 190 countries for users of diverse economic backgrounds, making it more popular than iOS devices (Android developers n.d.).The project “KSUSoy YieldCalc” adopted the Android platform as its base to serve farmers, agronomists, and consultants and deliver performance to save time and enhance farmers’ their confidence. The native application uses “conventional approach” of estimation of yield for calculations and eliminates the need for having Internet connection to access, thereby increasing the application’s flexibility. The project utilized Android Software Development Kit (SDK) as its development platform with extensive Java and Extensible Markup Language (XML) coding. The Department of Agronomy at Kansas State University (KSU) tested the application with promising results. Dr. Ignacio Ciampitti of the Department of Agronomy at KSU currently demonstrates the application to farmers. User feedback has been very satisfactory to date.
Keywords: Soybean; Android app; KSUSoy YieldCalc; Estimate of yield before harvest; Computing and Information Sciences; Agronomy; Computer Science (0984)